2018
DOI: 10.1002/adhm.201801138
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Physicochemical Properties of Biomimetic Hydroxyapatite on the In Vitro Behavior of Endothelial Progenitor Cells and Their Interaction with Mesenchymal Stem Cells

Abstract: Calcium phosphate (CaP) substrates are successfully used as a bone grafts due to their osteogenic properties. However, the influence of the physicochemical features of CaPs in angiogenesis is frequently neglected despite it is a crucial process for bone regeneration. The present work focuses on analyzing the effect of textural parameters of biomimetic calcium deficient hydroxyapatite (CDHA) and sintered beta-tricalcium phosphate (β-TCP) such as specific surface area (SSA), surface roughness and microstructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 73 publications
1
5
1
Order By: Relevance
“…VEGF-A followed the same expression pattern in both cell lines, peaking at day 1 followed by a sharp decrease at day 3. Upregulation at day 1 has been previously reported, since VEGF-A is an early angiogenic marker [48]. In contrast, VEGF-R2 and EDH-1 were only upregulated in hEPCs for the PDA@B/PDA@V-coated scaffolds.…”
Section: Angiogenic Gene Expressionsupporting
confidence: 61%
“…VEGF-A followed the same expression pattern in both cell lines, peaking at day 1 followed by a sharp decrease at day 3. Upregulation at day 1 has been previously reported, since VEGF-A is an early angiogenic marker [48]. In contrast, VEGF-R2 and EDH-1 were only upregulated in hEPCs for the PDA@B/PDA@V-coated scaffolds.…”
Section: Angiogenic Gene Expressionsupporting
confidence: 61%
“…In fact, the results of hMSCs proliferation on CDHA matured substrates, C and F (F > C), proved to surpass even that observed on TCPS at day 14 of culture ( Fig. 10 A) in contrast to previous results showing very limited cell proliferation on similar CDHA material [ 15 , 16 , 85 ]. The reason for the better performance of matured discs is reckoned to be, on one hand, the reduced effect of ion exchange as already explained [ 16 ] and, on the other hand, the favorable influence of protein adsorption on cell adhesion and proliferation [ 26 , 31 ].…”
Section: Discussioncontrasting
confidence: 66%
“…In terms of microstructure F-CDHA consisted of an entangled network of poorly crystalline needle-like nanometric crystals and C-CDHA of larger and more crystalline plate-like crystals. Previous in vitro studies on these materials showed impaired cell viability, especially for the more reactive F-CDHA due to the drastic alteration of the culture medium composition due to ionic exchanges [ 85 ], whereas excellent biocompatibility was found in vivo for both materials, F-CDHA showing superior osteoinductive and osteogenic properties [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of bone regeneration, the incorporation of tailored topographical features on to the surface of different biomaterials, including titanium [112][113][114][115][116][117][118], polycaprolactone [119,120], polystyrene [121], polyurethane [122], silica [122][123][124], poly(methyl methacrylate) (PMMA) [125][126][127], or calcium phosphates [128][129][130][131][132][133] has been extensively studied as strategies to induce osteogenesis of mammalian cells [134][135][136][137][138]. Recently, these topography-based strategies have been also studied in the context of antimicrobial biomaterials.…”
Section: Effect Of Topographymentioning
confidence: 99%